2021
DOI: 10.1016/j.ijrobp.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Radiation Dose to the Atherosclerotic Plaque in the Left Anterior Descending Coronary Artery for Radiation-Induced Cardiac Toxicity of Breast Cancer Patients?

Abstract: Radiation-induced acute coronary events (ACEs) may occur as a treatment-related late adverse effect of breast cancer (BC) radiation. However, the underlying mechanisms behind this radiation-induced cardiac disease remain to be determined. The objective of this study was to test the hypothesis that radiation dose to calcified atherosclerotic plaques in the left anterior descending coronary artery (LAD) is a better predictor for ACEs than radiation dose to the whole heart or left ventricle in patients with BC tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…Though ionizing radiation to the heart is known to induce cardiovascular injury through sustained inflammation, leading to atherothrombosis after decades of RT [ 29 ], it remained unknown whether there was an interaction between preexisting coronary plaques and radiation exposure in ACEs development. In addition to one animal study that radiation accelerates atherosclerosis [ 30 ], Bogaard et al reported clinical data that the mean radiation dose delivered to atherosclerotic plaques was the ACEs' strongest predictor in breast cancer patients [ 16 ]. Our results support these findings, as all ACEs were detected in patients who received RT, and the ACEs' specific locations in patients with a CAC score >0 were areas where calcified coronary plaques were present before RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though ionizing radiation to the heart is known to induce cardiovascular injury through sustained inflammation, leading to atherothrombosis after decades of RT [ 29 ], it remained unknown whether there was an interaction between preexisting coronary plaques and radiation exposure in ACEs development. In addition to one animal study that radiation accelerates atherosclerosis [ 30 ], Bogaard et al reported clinical data that the mean radiation dose delivered to atherosclerotic plaques was the ACEs' strongest predictor in breast cancer patients [ 16 ]. Our results support these findings, as all ACEs were detected in patients who received RT, and the ACEs' specific locations in patients with a CAC score >0 were areas where calcified coronary plaques were present before RT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the application of a deep-learning software successfully reduced the time and labor required for manual CAC scoring, and a wider application of the scoring system was possible for selecting high-risk patients with ACE development among the general population [ 13 , 14 ]. In breast cancer patients, the CAC score was shown to be ACEs' predictive risk factor [ [15] , [16] , [17] ]; however, it remains unclear whether the CAC score and radiation exposure interact synergistically to exacerbate the ACEs’ risk.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, analyses on cardiac substructures dose, including the LAD, have been published ( 19 , 20 ). Zureick et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, radiation doses to LAD atherosclerotic plaques have also been studied and found to be the strongest predictor of acute coronary events (ACEs) amongst patients with established atherosclerotic disease, even after correction for cardiovascular risk factors https://doi.org/10.3857/roj.2021.00766 (hazard ratio [HR] = 1.269; 95% CI, 1.090-1.477; p = 0.002). However, the volume of the left ventricle receiving ≥ 5 Gy remains to be an essential predictor of ACEs in patients without atherosclerotic plaques in the LAD (n = 680) (HR = 1.021; 95% CI, 1.003-1.039; p = 0.023) [52].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Radiation doses above 30 Gy reportedly increased RIHD by three and a half folds [18,56]. Some of the studies about radiation-related risk factors are summarized in Table 1 [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Radiation-related Risk Factorsmentioning
confidence: 99%